Gramedia Bookstore Business Strategy: From "Brick and Mortar" To "Brick and Click" - Rini, Karina Prawita; Titus, Amol (The Indonesian Journal of Business Administration, 2015)
Gramedia Bookstores as a "brick & mortar" business model must face the threat of e-commerce and the emergence of online bookstores within and outside the country. E-commerce has become both a threat and an opportunity for PT. Gramedia Asri Media (PT. GAM) as the operator of Gramedia Bookstores. PT. GAM needs to innovate and develop their online bookstore in order to achieve sustainable advantage in the retail bookstore business. www.gramediaonline.com has been established since 2010 and has become one of the most reliable online bookstores in cyberspace. The efforts of PT. GAM in developing their online bookstore has been supported by good infrastructure and a variety of innovations to increase growth, however until this paper has been written, it has yet to reach Break Even Point (BEP), which was projected to be achieved in 2015 (the fifth year of operations). The data collection used in this Final Project consists of primary data obtained in the form of interviews, a questionnaire and direct evaluation of the online website. Secondary data were obtained from the financial statements and sales data of PT. GAM from 2011 to 2013. The significant factors affecting the stagnant growth of www.gramediaonline.com was evaluated based on literature data review and later analyzed to understand why www.gramediaonline.com has not developed according to expectations of PT. GAM’s management. This final project aims to propose a strategy to expand Gramedia Online to mitigate future negative loss which will result in the outcome of an implementation plan.According to the analysis, the result findings show important factors affecting the stagnant growth of www.gramediaonline.com caused by low reading interest in the general public, difficulties in accessing the internet, distrust of online shopping procedures, the inability to touch/see the book, low awareness of the Gramedia Online websire, lack of preparation to sell products through the website, and the incompetitive pricing of products on www.gramediaonline.com.The proposed strategies to increase sales of Gramedia Online are by improving the quality of human resources, improve www.gramediaonline.com website, increase promotional programs on www.gramediaonline.com, ensure strong support for Gramedia Online from critical suppliers, improve the pricing scheme of products sold, target business-to-business sales (corporate sales), and to develop new concepts for the purchase of school books content and apply an online subscription system to ease the high prices of the textbooks. The long term goal proposed by the author will be to slowly transform into a marketplace.Keywords: e-commerce, online bookstore, key factors, Indonesia